A STUDY ON EMPLOYEE RETENTION WITH SPECIAL REFERENCE TO MANNARKKAD MUNICIPALITY, PALAKKAD DISTRICT. - Fasla N.P (International Journal of Research Science and Management, 2017)
Employees are the most valuable assets of an organization. Today Employees are different. They are not the ones who do not have good opportunities, especially, experienced and talented ones. As soon as they feel dissatisfied with the current employer or the job due to lack of advancement opportunities, salary and remuneration and others, they switch over to the next. The result is that employers lose their invested resources to their competitors, corporate memory is lost, employee-customer relationships are strained and more over the moral of existing staff goes down. It is therefore very important that employers retain their employees, especially the good and experienced ones. Employee retention is a process in which employees are encouraged to remain with the organization for the maximum period of time or until the completion of a particular project. This paper looks forward the different factors determining employee retention and different motivational programme for employees.